Don't say a word - Fleder, Gary.; Douglas, Michael, 1944-; Bean, Sean.; Murphy, Brittany; Torry, Guy.; Esposito, Jennifer, 1972-; Janssen, Famke, 1964-; Platt, Oliver; Klavan, Andrew (Beverly Hills, Calif : Twentieth Century Fox Home Entertainment, 2001)
When the daughter of a prominent New York psychiatrist is kidnapped, his only hope for her safe return is to pry a 6-digit number from the memory of a troubled teenage girl--and time is running out.
Based on the book by Andrew Klavan.
Special features: Commentaries by Michael Douglas, Sean Bean, Brittany Murphy, Famke Janssen, Oliver Platt; Director's commentary; Deleted scenes; "Making of" featurette; Set tour featurette; Film scoring featurette; screening room dailies; Brittany Murphy screen test; Storyboard-to-Screen comparisons; Cast/crew bios.
Director of photography, Amir Mokri ; editors, William Steinkamp, Armen Minasian ; music, Mark Isham ; costume designer, Ellen Mirojnick ; production designer, Nelson Coates.
Michael Douglas, Sean Bean, Brittany Murphy, Skye McCole Bartusiak, Guy Torry, Jennifer Esposito, Famke Janssen, Oliver Platt.
DVD, Dolby DTS surround sound.
English or French dialogue; subtitles in English.
Keywords: Kidnapping victims -- Drama; Feature films; Thrillers (Motion pictures).